Percentage of glycosylated serum ferritin remains low throughout the course of adult onset Still's disease. Issue 5 (1st May 2000) - Vignes, Stéphane; Le Moël, Gisèle; Fautrel, Bruno; Wechsler, Bertrand; Godeau, Pierre; Piette, Jean-Charles
Abstract : OBJECTIVE: To determine the evolution of levels of total serum ferritin and percentage of the glycosylated form in patients with adult onset Still's disease (AOSD) at the time of diagnosis and during follow up. METHODS: All patients with AOSD were tested at the time of diagnosis and during follow up. Total serum ferritin levels were analysed by immunoassay, and the percentage of glycosylated ferritin was determined by methods using Sepharose-Con A. RESULTS: 14 patients (eight women, six men) with AOSD were enrolled. At the time of diagnosis, mean (SD) age was 36 (16) years. Mean initial total serum ferritin was 6350 (1300) μg/l (normal <250 μg/l). The mean initial percentage of glycosylated ferritin was 14.7 (13)% (normal >50%). Mean follow up time was 37 (35) months. At the time of the last examination all patients were in remission except one, who presented a chronic articular form. Total serum ferritin remained high in this single patient and was normal in the 13 others, with a mean of 98 (73) μg/l. In all patients the percentage of glycosylated ferritin remained low, with a mean of 16 (16)%. CONCLUSION: Total serum ferritin is a marker of the active phase of AOSD. The percentage of glycosylated ferritin is low both in the active phase and in remission. Further studies are needed to confirm these data and to determine their specificity for AOSD before considering any possible use of a low percentage of glycosylated ferritin as a diagnostic tool in suspected AOSD, especially when atypical or previously treated.